Increasing ratio of opportunistic infections associated with sunshine exposure and economic level burdening Chinese inflammatory bowel disease hospitalized patients: the first nationwide survey from 2014 to 2019 - Runing Zhou; Ruixian Wu; Li Wang; Hong Yang (BMC, 2024)
Abstract Background The rising prevalence of opportunistic infections (OIs) in inflammatory bowel disease (IBD) in conjunction with the use of biologics/immunosuppressive agents has garnered attention. However, there is a dearth of research on OIs in Mainland China. This study seeks to evaluate the national ratio trend of OIs in IBD and elucidate the influence of economic and climate factors on IBD patients with OIs and their outcomes. Methods The nationwide data was obtained from the Inpatient medical record home page via the Health Statistics and Information Reporting System (HSRS). Patients diagnosed with IBD were enlisted for participation, and their demographic and clinical information, encompassing infection type, surgical procedures, and expenses, were gathered. The National Bureau of Statistics provided data on monthly sunshine exposure hours and yearly Gross Domestic Product (GDP). Results Findings indicate that between 2014 and 2019, a total of 381,752 patients with IBD were admitted to hospitals, with 364,249 patients lacking OIs and 17,503 patients presenting with OIs. The annual proportion of OIs exhibited an upward trend, rising from 3.54% in 2014 to 4.81% in 2019. There was a significant correlation observed between individuals who identified as male, those who visited hospitals in southern regions, or those originating from areas with lower GDP or shorter sunshine exposure hours, and a higher incidence of OIs. Among patients diagnosed with either Crohn's disease (CD) or ulcerative colitis (UC), Clostridium difficile was found to be the most prevalent infection, followed by Epstein-Barr virus and cytomegalovirus. Furthermore, the occurrence of OIs was found to be associated with an increased rate of surgical interventions in UC patients. Conclusions The rising prevalence of OIs among hospitalized patients with IBD necessitates heightened attention towards mitigating associated risk factors, particularly among IBD patients residing in less developed regions or experiencing limited exposure to sunlight. This approach aims to minimize hospital stays and associated costs.